Experimental study on deformation of heavy metal contaminated expansive soil under cyclic loading. Issue 2 (February 2019) - Zhang, Yuguo; Zheng, Yanlin; Han, Shuai; Wan, Dongyang; Yang, Hanyue; Duan, Mengmeng
Abstract: Heavy metal pollution has received widespread attention at home and abroad as an important environmental engineering problem, and the research on the deformation characteristics of heavy metal contaminated expansive soil under cyclic loading is still in its infancy. According to the Nanyang expansive soil, the effects of a few factors including heavy metal ions concentration, dynamic stress amplitude, vibration frequency and confining pressure on axial cumulative deformation and critical dynamic stress for polluted expansive soil is studied. The results show that the cumulative axial strain has different development modes under different dynamic stress amplitudes, which can be divided into failure type, critical type and stable type. The same cumulative axial strain is achieved with the increase of heavy metal ion concentration, and the amplitude of dynamic stress is smaller. As the vibration frequency increases, the cumulative axial strain of the contaminated expansive soil decreases. The greater the confining pressure, the smaller the cumulative axial strain of the polluted expansive soil. The critical dynamic stress decreases with the increase of the heavy metal ions concentration, and under the same heavy metal ions concentration, the critical dynamic stress increases obviously with the increase of confining pressure.